Purification and Partial Characterization of Î±-Amylase Produced by a Thermo-Halophilic Bacterium Isolate PLS 75 - Teuku M. Iqbalsyah; Farah Fajarna; Febriani Febriani (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Bio-based industries require stable enzymes in a broad range of environmental conditions. Extremophiles have attracted more interests as the source of such enzymes, one of which is Î±-amylase. This study aimed to purify and characterize Î±-amylase produced by a thermo-halophilic bacterium PLS 75 isolated from underwater fumaroles. Ammonium sulfate precipitation results showed that the highest specific Î±-amylase activity (21.7 U/mg) obtained at 40-60% saturation level, with a purity of 7.7-fold of the crude extract with 16.2% yield. Further purification using DEAE Sepharose column chromatography increased the enzyme purity 11.1-fold of the crude extract with 7.1% yield. Specific activity after column chromatography purification was 31.3 U/mg. The pure enzyme had a low molecular weight of 14 kDa. The enzyme showed the highest activity at 80 Â°C and pH 5. The activity increased to 126% when in methanol, while decreased when in ethyl acetate and chloroform. The characteristics of Î±-amylase with low molecular weight, which was active in acidic condition, stable in polar and non-polar solvents, may be used for for specific industrial needs.